2016
DOI: 10.1097/ta.0000000000001068
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of extracorporeal membrane oxygenation improves survival in adult trauma patients with severe adult respiratory distress syndrome

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 18 publications
9
93
2
Order By: Relevance
“…In addition, the National Inpatient Sample (NIS) showed a 66‐fold increase in the number of patients with trauma receiving ECMO support from 2002 to 2012 10 . This rapid adoption of ECLS may be in large part due to results of the CESAR trial, as well as dedicated studies in trauma cohorts, that demonstrated survival benefit for patients with ARDS 7,9,11,12 . The survival rate in our cohort, which approaches 60%, is comparable to patients with trauma in the ELSO registry (50%‐63%) and the NIS (52%) 10,13 …”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, the National Inpatient Sample (NIS) showed a 66‐fold increase in the number of patients with trauma receiving ECMO support from 2002 to 2012 10 . This rapid adoption of ECLS may be in large part due to results of the CESAR trial, as well as dedicated studies in trauma cohorts, that demonstrated survival benefit for patients with ARDS 7,9,11,12 . The survival rate in our cohort, which approaches 60%, is comparable to patients with trauma in the ELSO registry (50%‐63%) and the NIS (52%) 10,13 …”
Section: Discussionmentioning
confidence: 63%
“…Extracorporeal membrane oxygenation (ECMO) in patients with trauma is most commonly used for refractory hypoxemia and severe acute respiratory distress syndrome (ARDS) 4 . This modality appears to be safe and may offer a survival benefit when conventional ventilatory therapies fail 5–7 . Geographic access to high‐performing centers with ECMO capabilities, however, varies considerably across the United States 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of ECMO is usually based on the severity of ARDS, as represented by severe hypoxemia despite high PEEP (PaO 2 /FiO 2 < 80 mmHg) and uncompensated hypercapnia (pH < 7.2) [22]. There is evidence that early initiation of ECMO (1.9 ± 1.4 days after onset of severe ARDS defined by Berlin definition) improves survival in trauma patients [23]. However, this study is limited by small sample size and the use of historical control.…”
Section: Timing Of Ecmo Initiation: Indications From Ventilation Pmentioning
confidence: 99%
“…Another method is to increase the ability of a given patient to tolerate the disease, i.e., target host resilience mechanisms. So far this has largely been in the form of supportive care, which relies on mechanical ventilation and oxygenation [29,39,66].…”
Section: Host Resilience To Sars-cov and Mers-covmentioning
confidence: 99%